MODIFIKASI ALAT LATIHAN UNTUK LEMPAR LEMBING - Pratiwi, Santika Bunga; Samodra, Y. Touvan Juni; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed to modify a drills tool which named German Strength Training Device-Javeline Specific. These tools were modified in a simple form to be portable tools, so it can be overhauled, accompanied with the load and height of the corner throw that can be controlled. The research  method used was research and development (R&D), with several stages implemented were: identification potential and problems, collecting data, product manufacturing, expert validation, product revision, product trial and usage trial.  Modification the drills tool  for javelin throw formerly had already validated by the expert of the material, 2 practitioner experts, 7 respondents for product trial and 30 respondents for usage trial. The subject of the trial was students (at university) from sports coaching education. Data collection techniques in this study were instruments in the form of questionnaires which were analyzed by way of criteria exegesis descriptive measurements. The result research was in the form of a modification product used as means javelin throw drills. The result of the average of the assessment can be seen  from material expert was 86, practitioner experts was 93,7, product trial was 92,6 and result of usage trial was 92,9. Therefore, it can be concluded that modification of the drills tool for the javelin throw had properly suitable as a help tool for drills.Keywords: Javelin Throw, The Drills Tool,